Cycloelatanene A and B: absolute configuration determination and structural revision by the crystalline sponge method - Lee, Shoukou (Royal Society of Chemistry, 2017)

(untitled) (Chem Sci)
Cycloelatanene A and B are marine natural products first reported a few years ago. Their relative structures had been elucidated by an extensive NMR study and found to be epimers. However, their absolute configurations had not been established because they were isolated in only minute quantities as oily compounds. In this study, the complete structures of cycloelatanene A and B, including absolute configurations, were determined by the crystalline sponge method. The structure analysis confirmed the unique tricyclic structure involving a spiro[5.5]undecene skeleton. One stereogenic centre at C4 was revised as a result of this analysis. Since it only took 1–2 weeks to complete the experiments using the crystalline sponge method (guest-soaking followed by crystallographic analysis), this method is now highly recommended as a first port of call to achieve complete natural product structure elucidation.